Clinical and Demographic Characteristics of Dengue Patients in Public Sector Hospital - Dhiloo, Azizullah Khan; Ansari, Madiha Sattar; Tanzil, Sana; Zain, Nazima; Abbasi, Amanullah (Journal of Liaquat University of Medical & Health Sciences, 2024)
OBJECTIVE: To determine the patterns of demographics, clinical presentation, and outcome among dengue patients treated at Dr. Ruth K.M. Pfau Civil Hospital, Karachi. METHODOLOGY: This retrospective cross-sectional study comprised 1003 suspected dengue cases presented at Dr. Ruth K. M. Pfau Civil Hospital, Karachi, between September 2019 and February 2020. Medical records of 328 patients who tested positive for dengue infection on immune chromatographic technique (ICT) for recombinant NS1 antigen and/or IgM serology were included in the analysis. RESULTS: Among 1003 suspected cases, 328 cases were laboratory-confirmed dengue fever; 82.3% (n=270) presented with acute dengue infection as they were positive for NS1 antigen only. 13.1% (n=43) of the patients were IgM-positive, whereas 0.9% (n=3) were positive for IgG. 3.6% (n=12) of the laboratory-confirmed dengue patients were positive for both NS1antigen and IgM. The majority of the dengue patients were from the district of South Karachi. Among all in-patients, 77 % (n=94) of the patients presented uncomplicated dengue fever, while 21.3% (n=26) of hospitalized dengue patients presented with dengue hemorrhagic fever. However, 1.6% (n=2) of hospitalized patients presented with dengue shock syndrome. Mortality was 1.6% (n=2). CONCLUSION: We conclude that the epidemiology of dengue infection and seasonal disease variability in Pakistan's urban settings has not changed over the last decade but warrants continuous monitoring due to climate change. The disease is still more prevalent among young males with a classic presentation of dengue fever. Dengue hemorrhagic fever is relatively less common, while very few patients develop dengue shock syndrome, contributing to mortality.